2018
DOI: 10.3390/su10061766
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Evolution of Sustainable Urbanization Development: A Perspective of the Coupling Coordination Development Based on Population, Industry, and Built-Up Land Spatial Agglomeration

Abstract: A series of negative effects of urban development have emerged owing to the imbalance of population, industry, and built-up land spatial agglomeration. This study proposes an integrated coupling coordination index system in sustainable urbanization evaluation based on population, industry, and built-up land, to evaluate the spatial-temporal evolution of coupling and coordination degree in Guangxi from 2005 to 2015. In addition, we adopted the exploratory spatial data analysis method to reveal the spatial patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 81 publications
1
40
0
Order By: Relevance
“…This paper used Ha-Chang urban agglomeration as the research area, applied the econometric model of time series to study the interaction between population and land urbanization of Ha-Chang urban agglomeration, and applied the coordinated development degree model to analyze and evaluate the coordination development of population and land urbanization. In addition, exploratory research is an important measure to reveal the condition of urbanization development and discover the spatial heterogeneity of coupling coordination degree on sustainable urbanization [64]. According to the results of this research, we found that the industrial base of small-and medium-sized cities is weak.…”
Section: Discussionmentioning
confidence: 76%
“…This paper used Ha-Chang urban agglomeration as the research area, applied the econometric model of time series to study the interaction between population and land urbanization of Ha-Chang urban agglomeration, and applied the coordinated development degree model to analyze and evaluate the coordination development of population and land urbanization. In addition, exploratory research is an important measure to reveal the condition of urbanization development and discover the spatial heterogeneity of coupling coordination degree on sustainable urbanization [64]. According to the results of this research, we found that the industrial base of small-and medium-sized cities is weak.…”
Section: Discussionmentioning
confidence: 76%
“…Specifically, from the ecological dimension, this production mode has exerted too much pressure on the environment and broken the general laws of nature, leading to extreme weather and unusual nature activities. From the social dimension, this production mode has exposed human beings to serious industrial pollution such as air pollution, climate change, and heat island effect, which is threatening public health [58]. Meanwhile, from the economic dimension, this production mode has greatly decreased the efficiency of material and energy usage and produced a huge financial loss in light of the enormous scale of China's industrial sector.…”
Section: Discussionmentioning
confidence: 99%
“…As a tool for assessing two or more systems, the coupling coordination degree is a combination of the coupling degree and coordination degree. Coupling originates from physics and refers to the phenomenon in which two or more systems interact with each other in various ways to achieve synergies [70]. In this study, the coupling degree is the level of nonlinear relationships of mutual interactions between CTI.…”
Section: Model Of the Coupling Coordination Degreementioning
confidence: 99%